2007
DOI: 10.1097/01.gme.0000227859.50473.20
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring reproductive aging in a 5-year prospective study

Abstract: Aggregate-level data do not reflect differences across women and oversimplify the age-related increases and variability in LH and FSH. Individual FSH levels are not distinguishable from reproductive-age levels until after rapid perimenopausal increases in FSH occur; individuals vary in whether their postmenopausal LH levels are distinguishable from reproductive-age levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Consistent with our findings, previous studies with longitudinal data have shown that levels of LH and FSH increase with reproductive and chronological age at least up to the early postmenopause, and that postmenopausal www.nature.com/scientificreports/ levels of these hormones remain higher than premenopausal levels [8][9][10]25,37 . However, across our and other studies, there is variation in whether, after a period of increase, levels then appear to remain stable [8][9][10] or decline 13,38 ; if there is a decline, the age at which this occurs seems to vary.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, previous studies with longitudinal data have shown that levels of LH and FSH increase with reproductive and chronological age at least up to the early postmenopause, and that postmenopausal www.nature.com/scientificreports/ levels of these hormones remain higher than premenopausal levels [8][9][10]25,37 . However, across our and other studies, there is variation in whether, after a period of increase, levels then appear to remain stable [8][9][10] or decline 13,38 ; if there is a decline, the age at which this occurs seems to vary.…”
Section: Discussionsupporting
confidence: 92%
“…The normal process of reproductive ageing varies considerably among women. While some women undergo premature menopause, others have spontaneous pregnancy in their fourth decade of life [ 1 ]. This variability, currently not predictable, is summarized in the concept of ovarian reserve, a term coined more than 25 years ago by Daniel Navot [ 2 ] and present in titles of at least 1300 papers indexed on PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…1318 AMH and inhibin B decline and FSH rises as a woman moves through the menopausal transition. 1921 The levels of AMH and FSH mark later stages of reproductive aging such as early perimenopause, late perimenopause, and postmenopause. 13, 2226 AMH is predictive of time to menopause.…”
Section: Introductionmentioning
confidence: 99%